In-plane Response of Masonry Infill Walls: Experimental Study using Digital Image Correlation. (2015) - Furtado, André; Ramos, T.; Rodrigues, Hugo; Arêde, António; Varum, Humberto; Tavares, P.
Abstract: The behaviour of the infill masonry (IM) walls in the reinforced concrete (RC) buildings has been subject of numerous numerical and experimental studies with the main purpose of characterizingtheir influence in buildings' response under seismic loadings. Although being considered non-structural elements, during an earthquake this type of elements tends to interact with the reinforced concrete surrounding frames, which canresult in different types of in-plane damage, namely diagonal cracking, corner crushing, shear-friction failure which significantly reduce the out-of-plane performance of such type of elements. In order to studythe in-plane behaviourof IM walls and its interaction with the surrounding frames, a full scale experimental test involving a double leaf infill panelwas carried out in the Laboratory of Earthquake and Structural Engineering – LESE. In addition, aDigital Image Correlation (DIC) technique was used and to monitor the experimental test response aiming at validating the potential of DIC as a non-contact, full-field, optical tool to measure displacement fields of both in-plane (2D) and out-of-plane (3D) structural motions. DIC consists on recording images at different stages of a test, with dissimilar perspectives, by dividing them in small sections, or subsets, and tracking their displacements along the different captured images. This research paper presents the in-plane experimental test and the results of the DIC technique application.